Probing numerical Laplace inversion methods for two and three-site molecular exchange between interconnected pore structures - Silletta, Emilia V.; Franzoni, María B.; Monti, Gustavo A.; Acosta, Rodolfo H. (Journal of magnetic resonance (1997), 2018)
[Display omitted] •T2-T2 NMR experiments are useful to study molecular exchange in porous media.•2D NMR experiments were successfully applied to organic materials.•Two algorithms for data processing by Numerical Laplace inversion methods are tested under several conditions.•Analytical results are confronted to numerical and experimental results. Two-dimension (2D) Nuclear Magnetic Resonance relaxometry experiments are a powerful tool extensively used to probe the interaction among different pore structures, mostly in inorganic systems. The analysis of the collected experimental data generally consists of a 2D numerical inversion of time-domain data where T2-T2 maps are generated. Through the years, different algorithms for the numerical inversion have been proposed. In this paper, two different algorithms for numerical inversion are tested and compared under different conditions of exchange dynamics; the method based on Butler–Reeds–Dawson (BRD) algorithm and the fast-iterative shrinkage-thresholding algorithm (FISTA) method. By constructing a theoretical model, the algorithms were tested for a two- and three-site porous media, varying the exchange rates parameters, the pore sizes and the signal to noise ratio. In order to test the methods under realistic experimental conditions, a challenging organic system was chosen. The molecular exchange rates of water confined in hierarchical porous polymeric networks were obtained, for a two- and three-site porous media. Data processed with the BRD method was found to be accurate only under certain conditions of the exchange parameters, while data processed with the FISTA method is precise for all the studied parameters, except when SNR conditions are extreme.